Nurses' Experiences of their Ethical Responsibilities during Coronavirus Outbreaks: A Scoping Review. Issue 3 (September 2022) - Peter, Elizabeth; Variath, Caroline; Mohammed, Shan; Mitchell, Mikaela; Killackey, Tieghan; Maciver, Jane; Chiasson, Conor
Globally, nurses have experienced changes to the moral conditions of their work during coronavirus outbreaks. To identify the challenges and sources of support in nurses' efforts to meet their ethical responsibilities during SARS, MERS, and COVID-19 outbreaks a scoping review design was chosen. A search was conducted for eligible studies in Ovid MEDLINE, Ovid Embase and Embase Classic, EBSCO CINAHL Plus, OVID APA PsycInfo, ProQuest ASSIA, and ProQuest Sociological Abstracts on August 19, 2020 and November 9, 2020. The PRISMA-ScR checklist was used to ensure rigor. A total of 5204 records were identified of which 41 studies were included. Three themes were identified related challenges in meeting ethical responsibilities: 1) substandard care, 2) impeded relationships, 3) organizational and system responses and six themes relating to sources of support: 1) team and supervisor relationships, 2) organizational change leading to improved patient care, 3) speaking out, 4) finding meaning, 5) responses by patients and the public, 6) self-care strategies.Our review revealed how substandard care and public health measures resulted in nurses not being fully able to meet their ethical responsibilities of care. These included the visitation policies that impeded the support of patients by nurses and families, particularly with respect to face-to-face relationships. Organizational and system responses to the evolving outbreaks, such as inadequate staffing, also contributed to these challenges. Supportive relationships with colleagues and supervisors, however, were very beneficial, along with positive responses from patients and the public